Pick a picture, write a report! - McCurry, Kristen (North Mankato, Minnesota A+ Books are published by Capstone Press, 2014)
Introduces report writing to children using photographs as idea prompts"-
A gift from book Africa
The world around us
1 2 11 13
NEW_ZTN_GN
Keywords: Photographs -- Juvenile literature; Report writing -- Juvenile literature